A gas-phase coupling process for simultaneous production of γ-butyrolactone and furfuryl alcohol without external hydrogen over bifunctional base-metal heterogeneous catalysts. Issue 8 (1st February 2016) - Hu, Qi; Fan, Guoli; Yang, Lan; Cao, Xinzhong; Zhang, Peng; Wang, Baoyi; Li, Feng
Abstract : A solvent-free gas-phase coupling process through hydrogen transfer without external hydrogen was conducted over novel bifunctional base-metal heterogeneous catalysts. Abstract : A solvent-free gas-phase coupling process through hydrogen transfer without external hydrogen supply over novel bifunctional base-metal heterogeneous catalysts was developed for the simultaneous production of γ-butyrolactone and furfuryl alcohol with high yields of 95.0% from biomass-derived compounds. Such a practical, unparallely efficient and environmentally benign process makes it promising in terms of both green sustainable chemistry and industrial perspective.